2015
DOI: 10.2166/wh.2015.271
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Pb(II) adsorption on nanostructured γ-alumina: calculations of axial dispersion and overall mass transfer coefficients in the fixed-bed column

Abstract: In the present study, the removal of metal ions Pb(II) using nanostructured γ-alumina was investigated by tests on batch operations and fixed-bed columns. Optimization was determined for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Flow rates of 20 and 40 mL/h were used. In Table 3 it can be noticed that by raising the column height the breakthrough time and the values of q b and q 50 increased because of the larger amount of active groups which are the cause of the removal (Chen et al, 2012;Saadi et al, 2015;Che-Galicia et al, 2014).…”
Section: Effect Of Column Heightmentioning
confidence: 97%
“…Flow rates of 20 and 40 mL/h were used. In Table 3 it can be noticed that by raising the column height the breakthrough time and the values of q b and q 50 increased because of the larger amount of active groups which are the cause of the removal (Chen et al, 2012;Saadi et al, 2015;Che-Galicia et al, 2014).…”
Section: Effect Of Column Heightmentioning
confidence: 97%
“…However, Pe would be larger if the interstitial velocity, which can be determined using membrane porosity, was used for the calculation. Other studies have reported larger D a values ranging from 1.5 × 10 –9 to 4.0 × 10 –6 m 2 s –1 for various divalent metals, which would lead to significantly lower Pe numbers. Even though similar studies for uranyl ion were not widely reported, columns packed with sand and crushed granite resulted in D a values of (1.4–3.4) × 10 –7 and 4.4 × 10 –5 m 2 s –1 for uranium­(VI).…”
Section: Resultsmentioning
confidence: 94%